Chapter Moth-Like Chemo-Source Localization and Classification on an Indoor Autonomous Robot - Mathews, Zenon; Bermúdez i Badia, Sergi; Marcos, Encarni; Escuredo Chimeno, Alex; Vouloutsi, Vasiliki; López, Lucas L.; Verschure, Paul F. M. J.; Ziyatdinov, Andrey; Perera i Lluna, Alexandre (InTechOpen, 2021)
Medical genetics